Islam dan Budaya: Strategi Kultural Walisongo dalam Membangun Masyarakat Muslim Indonesia - Suparjo Suparjo (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2008)
This paper intends to analyze how Walisongo applied their cultural strategies to construct Indonesia Muslimsociety. It aims to give an alternative view in solving the discourse on the effective impact of cultural strategy in constructingsociety. To do so, it applies a socio-historical perspective. As a result, Walisongo successfully constructed Muslim society as aninclusive and transformed people towards local cultures. However, Walisongo did not apply syncretism or integrationbetween Islam and local culture but they just acculturated some of Islamic doctrine within local cultures. Therefore, therewere many elements of local cultures adopted by Walisongo as elements of Islamic cultures by internalizing Islamic doctrineswithin them. Since Walisongo’s cultural strategy successfully played an important role in constructing society, the question thencould it be adopted until nowdays?